Functional outcome of limited contact dynamic compression plating and interlocking nailing for fracture shaft of humerus in adults - Vivian Roshan D'Almeida; Ashwin Kamath; Akhil Xavier Joseph; Alfred Manoj Lobo; Tilak Rommel Pinto (Wolters Kluwer Medknow Publications, 2023)
Background: Fractures of shaft of humerus are common, accounting 3% of all fractures. They have historically been managed conservatively with hanging casts or a functional brace. However, a lack of fracture reduction with these conservative measures resulted in malunion. Two surgical techniques under study include intramedullary nailing and limited contact dynamic compression plating. This study aims to analyze the functional outcome between the two surgical techniques. Materials and Methods: In this prospective randomized study, 38 patients were treated surgically for shaft of humerus fracture from August 2016 to August 2018 at a tertiary care center. Twenty patients underwent limited contact dynamic compression plate (LCDCP) plating and 18 underwent intramedullary nailing. All were assessed for radiological union, complications, and functional outcome at 6 weeks, 12 weeks, and 1 year using disabilities of arm, shoulder, and hand (DASH) questionnaire. Results: Thirty-eight patients completed the study of which 18 cases (47.5%) with fractures that were treated with interlocking nail and 20 cases that were treated with LCDCP plating. The mean duration to complete radiological healing was 15.06 weeks. The healing rate was relatively faster in the interlocking group as compared to the LCDCP group (P = 0.144). Complications such as shoulder impingement 8 (44.4%), shoulder pain 3 (16.7%), nonunion 1 (5.6%), and shoulder stiffness 1 (5.6%) were found to be more common in interlocking group as compared to LCDCP group, respectively. Whereas, complications such as superficial infection - 1(5%) and radial nerve deficits - 2(10%) were less common in the interlocking group compared to LCDCP group, respectively. The mean follow-up was 11.556 weeks, and the overall DASH score analysis showed better results in LCDCP group. Conclusion: In our study, LCDCP plating showed lower incidence of complications, particularly periarticular complications around the shoulder joint such as shoulder pain, stiffness, and impingement but carried a higher risk of radial nerve injury. Fracture union rates were found to be almost similar between both groups. DASH score analysis showed better functional outcome among the LCDCP plating group. The overall outcome of LCDCP plating over interlocking nailing was found to be better.